Novel Insight of CircRNAs in Cervical Cancer: Potential Biomarkers and Therapeutic Target - Wu, Maomao; Han, Yanxun; Gong, Xiangfei; Wan, Ke; Liu, Yuchen; Zhou, Yi; Zhang, Lizhi; Tang, Guozheng; Fang, Hui; Chen, Bangjie; Yang, Fan; Zhao, Qing; et al. (Frontiers in Medicine, 2022)
Cervical cancer (CC) is a prominent cancer around the globe, with a high incidence, and fatality rate. Numerous recent investigations have shown that various non-coding RNAs are associated with the progression of CC. Circular RNAs, a novel class of non-coding RNAs, have a single chain covalent closed-loop structure and are involved in cell growth and other physiological processes. These dysregulated circRNAs seem to have environment-specific functions. They have been demonstrated in certain studies to have a dual involvement in oncogene production and tumor inhibition in different cell settings. Simultaneously, some evidence indicates that circRNAs are abnormally expressed in CC and contributes to its progression. Thus, the distinctive expression profile of circRNAs is associated with the diagnosis, prognosis, and treatment outcomes of CC. We summarized numerous CC-specific circles and their function in revealing the molecular processes of carcinogenesis and progression in CC in this review. Taken together, these data suggest that circRNA may be used as an early detection biomarker and potential therapeutic target in patients with CC.